Das normas trabalhistas autônomas coletivamente negociadas: sua interpretação autêntica no contexto da pós-modernidade, à luz da hermenêutica fenomenológica - Daniel José Fonseca Mendonça (2021)
Man, as a social being, has always had a tendency towards associativism, whether for sharing or defending the common interests of group members. This type of behaviour was not different in discussions regarding to work issues, which is why class associations have been part of the evolution of humanity for millennia. In addition to being social, man is also a political being, so, although workers' associations are a form of instinctive manifestation, there were times when they were socially instituted and others when they were prohibited, until today, when they are widely recognized as a human right. The development of the State in modernity has changed the way in which workers' associations work, which are currently represented mainly by labour unions. From the French Revolution onwards, the ideals of freedom and the evolution of capitalism as an economic system were determining factors for conciliation of the different interests existing between the unions representing the classes of workers and those representing holders of the means of production. Then, negotiations between these groups are recognized by the legal system as autonomously instituted norms. The strong influence of capital on the structure of the modern State has always interfered not only with these collectively negotiated norms, but also with the state legislation that regulates them and the way in which they are judicially interpreted. The research presented here will delve into the controversies and its nuances that are involved in negotiated norms by the worker’s and economical classes. The study will be held through phenomenological hermeneutics, which will have as its object the Constitution, the common and especial Legislation regarding to workers collective negotiations. The purpose of this study is to demonstrate the importance of an authentically done interpretation aiming to unveil this legal phenomenon, bringing its features to consciousness and seeking that, in the end, it will have a an hermeneutics answer favorable to the development of the Collective Labour Law.